Operative Techniques in Laryngology - Rosen, Clark A. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Operative Techniques in Laryngology fills a void that currently exists in otolaryngology textbooks: a comprehensive text on laryngeal surgery that can be used by physicians to prepare for surgical cases. It contains explicit step-by-step descriptions of surgical procedures such that the reader can “learn to operate”. The surgical atlas is written by well-known experts with step-by-step surgical maneuvers for various laryngeal procedures encompass both microlaryngeal surgery and laryngeal framework surgery. Postoperative care and complications are also covered to round out the information needed by the surgeon in the perioperative period. The atlas is richly illustrated with photographic representations of all surgical steps and superb artwork illustrations to highlight the difficult three-dimensional anatomic concepts. In summary: This unique guide filled with “cookbook” descriptions of laryngeal surgical procedures provides a quick and simple reference for all surgeons interested in laryngological surgery.